Modality in the digital age. (August 2018) - Ravelli, Louise J; Van Leeuwen, Theo
Kress and Van Leeuwen's book Reading Images: The Grammar of Visual Design (2006[1996]) provides a robust framework for describing modality in visual texts. However, in the digital age, familiar markers of modality are being creatively reconfigured. New technological affordances, including new modes of production, multiple platforms for distribution, and increased user control of modal variables, raise questions about the role of modality in contemporary communication practices and require the framework to be adapted and further developed. This article attempts to set the agenda for such adaptations and, more generally, for rethinking visual modality and its impact in the digital age.